Sosialisasi Hak Pekerja/Buruh yang Bekerja Pada UMKM di Desa Girisekar, Yogyakarta - Fakultas Hukum Universitas Negeri Surabaya; Ahmad Nailul Author; Arinto Nugroho (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, contributing more than 60% to the Gross Domestic Product (GDP) and employing around 97% of the national workforce. However, the lack of understanding among MSME entrepreneurs and workers regarding labour regulations often leads to violations of workers' rights, such as fair wages, social security, and occupational health and safety protection. This Community Service Programme (PKM) aims to improve the legal literacy and awareness of MSME entrepreneurs in Girisekar Village, Gunungkidul, through the dissemination of information on workers' rights as stipulated in laws and regulations. The implementation methods include pre-tests, legal counselling, and post-tests to measure the effectiveness of the activities. The expected results are an increase in MSME actors' understanding of their legal obligations and the creation of fairer and more productive working relationships. Thus, this programme is expected to support the sustainability of businesses and the welfare of workers in the MSME sector.